Application of the ALBI Scoring System for Mortality Outcome Prediction in Patients with Hypertrophic Cardiomyopathy. Issue 1 (11th October 2022) - Qiao, Ping; Li, Liying; Ruan, Haiyan; Zhang, Muxin; Wang, Ziqiong; Li, Xinran; Shi, Rufeng; Wei, Xin; Duan, Linjia; Zheng, Yi; He, Sen
Background: There is no information about the clinical significance of the albumin-bilirubin (ALBI) score in patients with hypertrophic cardiomyopathy (HCM). Objective: We retrospectively performed clinical evaluations in 462 patients with HCM to estimate whether the ALBI score could be a new tool to predict mortality in HCM. Methods and Results: During a median follow-up of 4.7 years, HCM-related death occurred in 52 (11.3%) patients. Overall, there was a significant positive association between ALBI score and HCM-related death (adjusted hazard ratio [HR]: 1.79 per one standard deviation [SD] increment, 95% confidence interval [CI]: 1.36–2.35). When the score was assessed as tertiles, the adjusted HRs of HCM-related death were 1.30 (95% CI: 0.42–3.99) for the tertile 2 and 4.43 (95% CI: 1.65–11.89) for the tertile 3, compared with the tertile 1. Stratified analysis and E-value analysis suggested the robustness of the above-mentioned results. Meanwhile, time-dependent ROC analysis showed ALBI score could discriminate HCM-related death at various time points (AUC ranges: 0.725–0.850). Furthermore, exploratory analysis indicated the dynamic changes of ALBI score also could predict HCM-related death. Finally, multiple linear regression analysis suggested some pathogenetic pathways associated with HCM-related adverse outcomes significantly correlated with ALBI score, and the pathways included inflammation, myocardial injury, nutritional status and some clinical characteristics, but not abnormal cardiac structure and function itself. Conclusions: Higher ALBI score is a strong independent predictor of HCM-related death in patients with HCM.